2006
DOI: 10.1007/s10508-006-9094-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex of Experimenter and Social Norm Effects on Reports of Sexual Behavior in Young Men and Women

Abstract: Past studies indicate that men generally report having had more sexual experience and sexual partners than women, as well as an earlier age at first intercourse. At least some of these findings may partially reflect different responses to certain contextual variables in research. College students (266 men and 463 women) were asked to anonymously report their sexual attitudes and behavior after reading one of three fictitious statements about research findings regarding gender differences in sexuality. Some pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 40 publications
4
29
0
5
Order By: Relevance
“…However, it must be noted that the effect size for the sex difference in total SRS scores was small. Previous research has also found that reported sexual risk taking behaviors have been found to be higher for men than for women (e.g., Laumann, Gagnon, Michael, & Michaels, 1994;Oliver & Hyde, 1993;Poppen, 1995;Seal & Agostinelli, 1996;Vollrath, Knoch, & Cassano, 1999), although more recent studies have not found significant differences between the sexes (e.g., Browning, Kessler, Hatfield, & Choo, 1999;Fisher, 2007;Paul, McManus, & Hayes, 2000;Pedersen, Miller, Putcha-Bhagavatula, & Yang, 2002). Sex differences in sexual risk taking have been explained by a number of theories, including adherence to traditional gender roles and gender scripts (Eagly, 1987;Herek, 1986;LaPlante, McCormick, & Brannigan, 1980), personality differences (e.g., Zuckerman, 2007;Zuckerman & Kuhlman, 2000), evolutionary theory (Buss, 1998;Wilson & Daly, 1993), and even social exchange theory (Baumeister & Vohs, 2004).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it must be noted that the effect size for the sex difference in total SRS scores was small. Previous research has also found that reported sexual risk taking behaviors have been found to be higher for men than for women (e.g., Laumann, Gagnon, Michael, & Michaels, 1994;Oliver & Hyde, 1993;Poppen, 1995;Seal & Agostinelli, 1996;Vollrath, Knoch, & Cassano, 1999), although more recent studies have not found significant differences between the sexes (e.g., Browning, Kessler, Hatfield, & Choo, 1999;Fisher, 2007;Paul, McManus, & Hayes, 2000;Pedersen, Miller, Putcha-Bhagavatula, & Yang, 2002). Sex differences in sexual risk taking have been explained by a number of theories, including adherence to traditional gender roles and gender scripts (Eagly, 1987;Herek, 1986;LaPlante, McCormick, & Brannigan, 1980), personality differences (e.g., Zuckerman, 2007;Zuckerman & Kuhlman, 2000), evolutionary theory (Buss, 1998;Wilson & Daly, 1993), and even social exchange theory (Baumeister & Vohs, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Sex differences in sexual risk taking have been explained by a number of theories, including adherence to traditional gender roles and gender scripts (Eagly, 1987;Herek, 1986;LaPlante, McCormick, & Brannigan, 1980), personality differences (e.g., Zuckerman, 2007;Zuckerman & Kuhlman, 2000), evolutionary theory (Buss, 1998;Wilson & Daly, 1993), and even social exchange theory (Baumeister & Vohs, 2004). Researchers, however, have pointed out the statistical improbability of such large sex differences, especially in sex partners, and suggested that the effects may be due to social desirability and adherence to gender roles in reporting (Brown & Sinclair, 1999;Fisher, 2007;Maticka-Tyndale, Herold, & Mewhinney, 1998). Some researchers have asserted that these findings occur simply because men are over-reporting their sexual behaviors, especially their number of sexual partners (Morris, 1993;Smith, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Women may perform similar gender role congruent responding when presented with sexual stimuli. In contrast to women, who may often underreport their previous sexual experience to match their perceived societal expectations, men may over-report their previous sexual experience to also match their perceived gender role (Fisher, 2007). A recent study found that men characterized by high levels of hypermasculinity and ambivalent sexism reported more sexual partners when they had a female experimenter administering the anonymous survey, than if they had a male experimenter.…”
Section: Sociological Influencesmentioning
confidence: 99%
“…For instance, in a recent study by Fisher (2007), men exaggerated their sexual experience and reported more sexual partners with female research assistants (but not with male assistants), in particular when first threatened in their masculine identity by having been told that women are nowadays more sexually permissive than men. Other studies use watching porn as a situational trigger.…”
Section: Situation-related Aspectsmentioning
confidence: 99%